Comparação dos ICPs das faixas de tráfego que constituem corredores de transporte coletivo versus ICPs das demais faixas - SARRAF, Carlos Kevin Trindade (2024)
The quality of the rolling condition of pavements represents an important aspect for urban mobility, especially on roads and exclusive public transport lanes. The Pavement Management System (SGP) is an important tool for maintaining the quality of the urban road network, promoting less use of public resources. However, the implementation of this system depends on carrying out surveys of defects present in the pavements. Therefore, the objective of this research is to evaluate the surface condition of the three-lane pavement with an exclusive lane in the city of Belém, as well as compare the results obtained for each traffic lane. To this end, a survey of pavement defects in the study area was carried out and the ICPs (Pavement Condition Index) of each traffic lane were calculated, based on the Sousa method (2021), which adapted the SHRP (Strategic Highway Research Program). Among the main results, the exclusive lanes presented a lower average ICP than the central lane and the left lane, being, respectively, 78.94, 87.21 and 89.19. The most critical section presented an ICP of 46.05 and the best sections presented an ICP of 91.67. The most frequent defects in the study area analyzed were wear (39.78%), permanent deformation (18.23%) and fatigue cracks (17.13%). In the exclusive lanes, the defects that occurred most were wear (24.24%), fatigue cracks (22.22%) and permanent deformations (17.17%). No significant linear correlation was detected between ICP and road elevation, nor between ICP and the number of bus lines that travel along the lane. Finally, it was concluded that exclusive bus lanes present a greater degree of deterioration compared to the others, therefore, they should be prioritized in maintenance and rehabilitation activities.